First report of the giant liver fluke (Fascioloides magna) in Slovenia and molecular species confirmation based on the ITS2 marker - Žele Vengušt, Diana; Kušar, Darja; Vengušt, Gorazd; Bandelj, Petra (Frontiers in Veterinary Science, 2025)
IntroductionThe giant liver fluke, Fascioloides magna, is a parasite that primarily infects wild and domestic ruminants. Originally from North America, it has been an invasive species in Europe since the nineteenth century. Of the three natural foci that have become established in Europe, the Danube floodplain forest is the one that is still spreading. The first outbreak of fascioloidosis in Slovenia described in this report indicates that red deer (Cervus elaphus), fallow deer (Dama dama), and roe deer (Capreolus capreolus) are the three wild ruminants affected by the parasite.Materials and methodsA total of 22 frozen deer livers (14 red deer, five fallow deer, and three roe deer) were subjected to necropsy, parasitological and molecular examinations. Molecular detection of the extracted parasites was performed using species-specific PCR and Sanger sequencing techniques.ResultsThe presence of F. magna was confirmed in all liver samples. The infected livers of red deer and fallow deer were characterized by marked enlargement and the development of pseudocysts and distinct black pigmented lines within the parenchyma, whereas the livers of roe deer were of normal size and contained only migratory paths.DiscussionThe first report and molecular confirmation of F. magna in red deer, fallow deer, and roe deer in Slovenia indicate a northward spread of the trematode along the eastern side of the Mura River. Hunters, veterinarians, and farmers should be made aware of the existence of F. magna in north-east Slovenia and encouraged to report any liver abnormalities in ruminants. Future research should aim to investigate the spread of F. magna, its origins and economic impact.